A suspected case of a multiple autoimmune syndrome in a poodle dog. Issue 2 (9th February 2022) - Lim, Dahye; Jin, Yunseok; Son, Youngmin; Oh, Taeho; Bae, Seulgi
Abstract: A 9‐year‐old castrated male poodle dog was presented with icterus, anorexia, and lethargy. The dog was diagnosed with hypothyroidism 1 month before and was treated with levothyroxine. Severe anaemia with spherocytes, positive saline agglutination test, and hyperbilirubinemia indicated immune‐mediated haemolytic anaemia (IMHA). Therefore, immunosuppressive therapy with prednisolone, mycophenolate mofetil, and danazol was started. Although the IMHA was well controlled, during tapering of prednisolone, acute multiple joint swelling and oedema suspected immune‐mediated polyarthritis occurred twice. First, clinical symptoms improved as the dosage of prednisolone increased. However, the dog showed severe adverse effects to the steroid. Second time, we added leflunomide as another immunosuppressant, and clinical signs of arthritis disappeared. About 3 weeks later, despite the immunosuppressive therapy, skin lesions resembling an autoimmune dermatologic disorder spread throughout the body. Addition of cyclosporine resolved the skin lesions. This is a case report of a dog showing several sporadic clinical signs related to multiple autoimmune syndromes and their management using different immunosuppressant drugs. Abstract : This is case report of a dog showing several sporadic clinical signs related to multiple autoimmune syndromes and their management using different immunosuppressant drugs.